Reassessing the assessment: exploring the factors that contribute to comprehensive financial risk evaluation - Carr, Nicholas (Kansas State University, 2014)
This dissertation explores the personal financial planning risk-assessment process. Specifically, the study has five main purposes: 1. Explore the associations among independent risk-assessment variables. 2. Explore the concept that prudent financial risk-assessment goes beyond estimating an individual’s risk tolerance. 3. Explore the impact that each risk variable has on an individual’s overall Comprehensive Risk Profile (CRP). 4. Construct a comprehensive method of risk-assessment to estimate an individual’s overall risk profile. 5. Develop a weighted risk profile score and assign it to a target asset allocation model. Risk-assessment is one of the most instrumental components of the financial planning process. Financial planners and advisors have a fiduciary, as well as a suitability, responsibility to assess the level of risk individuals should bear with respect to their financial plan (Morse, 1998). Because of this, the evaluation of one’s risk profile impacts the success of an individual’s financial plan. If the risk-assessment is accurate, financial goals will have a higher likelihood of being met. To date, little research in the personal financial planning field has attempted to model financial risk-taking behavior in a way that is useful for practitioners, academics, and policy makers. The literature has tended to focus on either models of risk-taking rooted in economic utility theory, or tests of hypotheses related to the association among demographic and socioeconomic factors and risk-taking (Grable & Lytton, 1998). Traditional economic models do not fully account for the role that personal, behavioral, and environmental factors play in influencing individuals’ behavior beyond maximizing their expected utility (Hanna & Chen, 1997). Researchers have yet to develop a risk-profiling system that uses these behavioral or personal factors, to describe an individual’s financial risk-taking framework. Ultimately, the results of this study will lead to a multidimensional, comprehensive, accurate method of risk-assessment for both academic researchers, as well as practitioners. The following will serve as the empirical model for the study.
Keywords: Financial planning; Risk tolerance; Risk assessment; Goals based planning; Risk profile; Financial risk assessment; Business (0310); Economics (0501); Economics, Finance (0508)